2018
DOI: 10.3390/molecules23010124
|View full text |Cite
|
Sign up to set email alerts
|

Single-Labeled Oligonucleotides Showing Fluorescence Changes upon Hybridization with Target Nucleic Acids

Abstract: Sequence-specific detection of nucleic acids has been intensively studied in the field of molecular diagnostics. In particular, the detection and analysis of single-nucleotide polymorphisms (SNPs) is crucial for the identification of disease-causing genes and diagnosis of diseases. Sequence-specific hybridization probes, such as molecular beacons bearing the fluorophore and quencher at both ends of the stem, have been developed to enable DNA mutation detection. Interestingly, DNA mutations can be detected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 95 publications
(102 reference statements)
0
19
0
Order By: Relevance
“…The brightest, previously reported fluorescent nucleobase analogs, such as tC o (ε × Φ ≈ 2,000 cm –1 M –1 ), , avoid PET quenching by having HOMO–LUMO energy levels that are intermediate between the HOMO of guanine and the LUMO of thymidine (Figure and Figure S1). However, the fluorescence intensity of tC o and related analogs exhibit little-to-no environmental sensitivity and therefore have limited utility as reporters of base pair mismatches. , Given the growing clinical interest in point-of-care detection of single nucleotide polymorphisms (SNPs), there have been numerous efforts toward the development of SNP sensors based on FBA-mismatch detection. , However, these attempts have thus far resulted in either bright FBAs with low sensitivity toward SNPs, or highly sensitive FBAs with low brightness. ,, Here we present the brightest and most sensitive FBA-mismatch reporter to date. The trans -stilbene-containing thymidine analog “ ts T” acts as an ideal molecular rotor for SNP detection, with a fluorescent lifetime (τ = 4–11 ns) that is slightly longer as compared to the time scale of local dynamic motions of base pair mismatches (0.1–10 ns). This provides unprecedented sensitivity and specificity for detecting a single adenine residue in the opposing strand, with an ∼20-fold brighter fluorescence intensity for matched “A” (ε × Φ = 3000–4250 cm –1 M –1 ) versus mismatched “C, T, and G” bases (ε × Φ = 150–520 cm –1 M –1 ).…”
mentioning
confidence: 99%
“…The brightest, previously reported fluorescent nucleobase analogs, such as tC o (ε × Φ ≈ 2,000 cm –1 M –1 ), , avoid PET quenching by having HOMO–LUMO energy levels that are intermediate between the HOMO of guanine and the LUMO of thymidine (Figure and Figure S1). However, the fluorescence intensity of tC o and related analogs exhibit little-to-no environmental sensitivity and therefore have limited utility as reporters of base pair mismatches. , Given the growing clinical interest in point-of-care detection of single nucleotide polymorphisms (SNPs), there have been numerous efforts toward the development of SNP sensors based on FBA-mismatch detection. , However, these attempts have thus far resulted in either bright FBAs with low sensitivity toward SNPs, or highly sensitive FBAs with low brightness. ,, Here we present the brightest and most sensitive FBA-mismatch reporter to date. The trans -stilbene-containing thymidine analog “ ts T” acts as an ideal molecular rotor for SNP detection, with a fluorescent lifetime (τ = 4–11 ns) that is slightly longer as compared to the time scale of local dynamic motions of base pair mismatches (0.1–10 ns). This provides unprecedented sensitivity and specificity for detecting a single adenine residue in the opposing strand, with an ∼20-fold brighter fluorescence intensity for matched “A” (ε × Φ = 3000–4250 cm –1 M –1 ) versus mismatched “C, T, and G” bases (ε × Φ = 150–520 cm –1 M –1 ).…”
mentioning
confidence: 99%
“…Taken together, the FITC labels promote little changes with a single incorporation to more significant increases in siRNA hybrid stability with the incorporation of multiple FITCs, suggesting a stabilizing effect, potentially due to π-stacking and n → π* interactions with adjacent nucleobases on the oligonucleotide strands. 30 , 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies on fluorescently labeled oligonucleotides have illustrated that covalent conjugation decreases fluorescence efficiency. 30 Upon conjugation of FITC with the siRNA sequences, a blue shift (485–445 nm) was observed. 31 UV absorption studies revealed an observed FITC absorption peak at around 460 nm (see Supporting Information, Figure S20 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiazole orange (TO, 2) is another common intercalator. It has a non-planar chromophore composed of a benzothiazole derivative and a quinolinium ring, linked via a methine bridge [2]. Thiazole orange is used as an intercalative transduction agent in nucleic acid hybridization assays.…”
Section: Introduction mentioning
confidence: 99%